LOCAL ANESTHESIA IN DENTAL PATIENTS AT RISK - Chuchula, N. V.; Chuchula, E. N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Local anesthesia for the patient’s general condition is the most important dental procedures. This article presents the classification and overview of integral components of modernlocal anesthetic drug. Represented the classification of local anesthetics, the absolute and relative contraindications and characteristics of use according to concomitant somaticpathology of the patient. Characteristics, the use in risk groups and contraindications of complex corpular components of modern local anaesthetic preparations are presented.